Perfil diferencial de linguagem oral, escrita e memória de crianças disléxicas e com dificuldade de aprendizagem - Barbosa, Thaís [UNIFESP] (2011)
Most children learn how to read and write with no problems, however, some face difficulties when acquiring and developing such skills. In the Brazilian population, instruments that assess academic competence indicate that many children do not achieve expected levels of reading and writing. However, this may occur due to several factors, such as biological, cognitive, emotional, familiar, socioeconomic and educational. Therefore, the aim of this study was to analyze and verify the profile of oral language, writing and memory of dyslexic children and differences in relation to children with learning difficulties. For such, two different studies have been conducted: In Study I, 47 children with dyslexia (DG), 41 age controls (AC) and 31 reading controls (RC) were assessed with a battery for evaluation of oral language, reading, writing, working memory and declarative memory. In this study, predominant changes were observed in the processing of phonological skills (phonological awareness, phonological working memory and rapid naming tasks) of the DG. Those changes were not associated to a delay, but to an atypical development of such skills, since children with dyslexia performed worse than RC. Another interesting finding was that vocabulary and low order phonological tasks (phoneme discrimination), demonstrated to be less relevant in the assessment of dyslexia. In reading and writing tests, the DG obtained lower scores from the simplest to the more complex tasks (letters, words, pseudowords and texts). This was also observed in other language tests (syntactic and oral sentence comprehension), which seem to be a result of changes in basic linguistic skills that interfere in cognitive skills of greater complexity. In Study II, 20 children with dyslexia (DG), 20 children with learning difficulties (LDG), 20 age controls (AC) and 20 reading controls were compared, using the same Study I battery. Results indicated that children with dyslexia obtained different profiles in oral language, reading, writing and memory, when compared to children with learning difficulties, even though both groups shared the same reading level. Main differences were observed in higher demand phonological skills, having the DG achieved lower scores. Therefore, children with dyslexia seem to present a different profile than those observed in children with learning difficulties. Furthermore, the present study indicates that the IQ/Achievement criterion was inefficient to identify children with dyslexia and consequently discriminate them from the learning difficulty group. This study also suggests that reading skills are distributed along a continuum, and dyslexia is located at the lower end of the curve.